Entrepreneurial learning at the boundary: How to learn from a local cheese maker - Lans, Thomas; Lubberink, Rob; Ploum, Lisa; Ammann, Marie; Gondwe, Sera (SAGE Publications, 2021)
The learning innovation we report in this article is an international rapid-prototyping event (48 hours) in which teams of international BSc and MSc students from two universities (Western Europe and South-East Africa, respectively) jointly designed and developed a prototype for a local small-business owner in a developing economy. The learning innovation has its origin in the simple observation that the majority of the current theories, cases, and learning activities that characterize entrepreneurship education have their origin in western-oriented epistemologies and ontologies. The goal of this entrepreneurial learning activity was to develop students’ entrepreneurial competencies through interaction and cross-boundary entrepreneurial problem-solving between university students from western and non-western origin. The results underpin that it is very worthwhile for higher education teachers—who look for new, cost-effective “wide” entrepreneurship education programs—to adopt such events. The results show that the program not only contributes to short-term impact (e.g., joy of learning and collaborating, confidence in the own expertise, and seeing where to contribute) but also enables longer term impact (e.g., moving from intention to an actual start-up). Moreover, the activity produces actual solutions that, in this case the cheese maker can implement, can help the business to grow and survive.